EFFECT ON THE RIPENING MAIZE HYBRIDS MORPHOLOGICAL PARAMETERS AND PERFORMANCE UNDER SPC "PODOLIE" - Рихлівський, І. П.; Вахняк, В. С.; Бурдига, В. М.; Строяновський, В. С. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The article reveals the relevance of the topic - the value of corn and its food; technical and fodder value. The effect of the rapidity of the maize hybrids on the onset of their growth and development phases; the biometric indices and biomass of hybrids of different maturity in FAO; the correlation between the vegetative organs of hybrids (stems; leaves; beginnings); their influence on the formation of the assimilation surface and the collection of dry substances. The average maize hybrids for 3 years formed the height of 239-242 cm; For each plant there were 9.45 to 10.7 leaves; and their vegetative mass was 423 to 437 c / ha; Weight of 1 plants - from 740 to 780 g; Leaf surface - from 45;5 to 49;5 thousand m2 / ha; The collection of solids from 1 hectare ranged from 243 to 534. In the laboratory; an analysis of the origins of maize hybrids were carried out; seeds of seed quality (1000 seed mass; germination energy and laboratory similarity) were determined. Structural analysis of corn hybrids has shown that the early-hybrid PR 39 N 32; based on indicators such as the mass of grain from the beginning; the number of seed rows in the beginning; the number of seeds per row and the weight of 1000 seeds; significantly outperformed other more recent-late hybrids. The economic efficiency of the corn yields was calculated: the highest yield was obtained in the earlyhybrid PR 39 H 32 (control version) - 12.9 t / ha; while for the other two it was Pustovarivsky and DK-315 it was 12.1-11.0 t / Ha; (correspondingly; the growth of its harvest to two other hybrids amounted to 0.8 - 1.9 t / ha). The cost of the crop on the control was 58050 UAH; which is higher by 3600-8550 UAH from other hybrids. At production costs of cultivation 28;900 UAH; the cost of 1 ts grain; according to the options; ranged from 224.0 to 262.7 UAH; and net income - from 20600 to 29150 UAH with a profitability of 101% on the control and 88- 71%; respectively; in other variants.